(untitled) (Research, Society and Development, 2021)
Objective: The aim of this research is to determine the prevalence of the effectiveness of the technique of suction therapy in low back pain of muscle origin, specifically in vendors of the trade Methods: This is a field research with application of questionnaires for data collection, application of the suction therapy protocol, where the data collection questionnaire was applied to salesmen of both sexes with low back pain, then performed the application of the Visual Analog Scale (VAS) at the beginning and just after each session evaluating the level of the patient’s pain, totaling 4 sessions in all, lasting about 15 to 20 minutes each session, having an interval of five to seven days between sessions. Conclusion: We conclude that the technique of suction cup therapy has significant results for the treatment of low back pain, showing positive results mainly at the end of the 4 sessions. However, new studies are necessary to better evidence the potential of the technique.